Direito à soberania alimentar e ao patrimônio cultural: perspectivas para uma alimentação identitária - Wolff, Ana Carolina [UNESP] (2015)
This paper is located in the overlapping of the human right to adequate food and the right to preservation of the sources of culture and Brazilian cultural heritage, considering the food culture as identity element in the choices about what, how, when, where and with whom you eat. Being the food a component of a people culture, the implementation of the human right to adequate food and the state of food and nutritional security of a country means much more than a number of meals a day, so that public policies should take into account the cultural dimension of food. Although Brazil has advanced in the fight against hunger, land concentration and the model of agricultural production do not create an environment conducive to the maintenance of cultural traditions in planting and consumption of food, so that the Brazilian food is every day more standardized and therefore reflects less and less their cultural identity. In this scenario, the fight is for food sovereignty, which is the right of peoples to decide on what to plant and what to eat, which only occur with an effective agrarian reform and public policies that favor family farming. In its obligation to preserve the sources of culture and cultural heritage food, the State should act in order to create conditions of continuity and residence of groups that holds the knowledge of a way to make related to the food, where is the culture, the real food and sustainability in the field and on the table of the Brazilians